Benchmarking CME Arrival Time and Impact: Progress on Metadata, Metrics, and Events. Issue 1 (3rd January 2019) - Verbeke, C.; Mays, M. L.; Temmer, M.; Bingham, S.; Steenburgh, R.; Dumbović, M.; Núñez, M.; Jian, L. K.; Hess, P.; Wiegand, C.; Taktakishvili, A.; Andries, J.
Abstract: Accurate forecasting of the arrival time and subsequent geomagnetic impacts of coronal mass ejections (CMEs) at Earth is an important objective for space weather forecasting agencies. Recently, the CME Arrival and Impact working team has made significant progress toward defining community‐agreed metrics and validation methods to assess the current state of CME modeling capabilities. This will allow the community to quantify our current capabilities and track progress in models over time. First, it is crucial that the community focuses on the collection of the necessary metadata for transparency and reproducibility of results. Concerning CME arrival and impact we have identified six different metadata types: 3‐D CME measurement, model description, model input, CME (non)arrival observation, model output data, and metrics and validation methods. Second, the working team has also identified a validation time period, where all events within the following two periods will be considered: 1 January 2011 to 31 December 2012 and January 2015 to 31 December 2015. Those two periods amount to a total of about 100 hit events at Earth and a large amount of misses. Considering a time period will remove any bias in selecting events and the event set will represent a sample set that will not be biased by user selection. Lastly, we have defined the basic metrics and skill scores that the CME Arrival and Impact working team will focus on. Key Points: We have fully defined metadata for CME arrival and impact and showed it is critical for assessment The validation event set will not be based on a handpicked set of events, but on two selected time periods We have identified metrics for CME arrival time and impact by community consensus